Professional Photostat Enterprise Taiping / Nursabrina Zulkefli - Zulkefli, Nursabrina (2021)
Professional Photostat Enterprise Taiping was established and began its operation in July 2015. The enterprise operates in the printing industry. The founding father of Professional Photostat Enterprise Taiping is Chen Wei Qi. He started his first operation with his wife, Ng Jia Hui. They are also assisted by their two children, who is Chen Xiu Ling and Chen Ming Huey. Since its inception, Professional Photostat Enterprise Taiping has been a leading enterprise in Taiping with interest and specialization in the printing industry and has become a fast-growing and profitable printing in Taiping with a proven track record in the printing industry. Its core business activity is printing and photocopies supplier, including large format printing and signage, garment printing, and graphic design services. Committed and an expert in retail printing business, Professional Photostat Enterprise Taiping offers a wide range of printing services with excellent customer service, high quality printing, fast print and low price. By synergizing wide range of printing market segments and printing technologies, Professional Photostat Enterprise Taiping continue to strive as a printing enterprise that offers over 600 printing products and services to customers. Today, Professional Photostat Enterprise serves 400 – 500 customers daily which include walk-in customers, SMEs, large operations, and government staff. Their employee’s unity inspires vibrant ideas, nurture potential, and deliver excellence in everything they do.